Economic Dynamics of Javanese Transmigrant Rubber Farmers in Sumber Rahayu, 1982–2011 (ETNOSIA : Jurnal Etnografi Indonesia, 2026)
In many transmigration areas, plantation commodities play a central role in shaping local economic structures. Most previous studies tend to focus on general socio-economic transformations or policy impacts, but rarely adopt a longitudinal or historical perspective that captures changes across extended periods of time. This study fills this gap. The study focuses on how transmigrant communities adapted their livelihood strategies and developed a rubber-based rural economy. Using historical and commodity-based approach, this study was conducted in Sumber Rahayu Village, Rambang District, Muara Enim Regency, South Sumatra, during 1982–2011. Data was collected through interviews with first-generation transmigrants, local community leaders, cooperative managers, and village officials, complemented by observation and document analysis, including transmigration records and village archives. The findings show that the initial phase of transmigration was marked by the failure of food-crop agriculture due to unsuitable environmental conditions, limited agricultural knowledge, and pest disturbances. These challenges encouraged transmigrant households to shift toward rubber cultivation, which was more compatible with local conditions and offered greater economic opportunities. The development of rubber plantations was further strengthened by the establishment of KUD Panca Mulya, which improved market access and price transparency. Although the rubber economy contributed to higher household welfare and infrastructure development, it also created vulnerabilities related to land ownership inequality, high production costs, and dependence on fluctuating commodity prices. It is argued in this article that transmigration was not merely a population redistribution program, but an adaptive socio-economic process that transformed frontier land into a commodity-based rural economy.
Keywords: rubber; transmigrant; plantation; transformation; farmers